Analysis of Online Loan Practices Among Generation Z from An Accounting Perspective - Bravian Shabri Titis Wicaksono; Danang Mintoyuwono (Green Publisher Indonesia, 2026)
This study is a quantitative study that aims to empirically examine the effects of financial literacy, financial behavior, and trust in online lending platforms on online lending practices among Generation Z in DKI Jakarta Province. The research sample was obtained using a purposive sampling technique involving Gen Z respondents who had previously used online lending services, resulting in a total of 55 respondents who met the research criteria. Hypothesis testing was conducted using partial least squares structural equation modeling (PLS-SEM) through SmartPLS version 4 software. The test results showed that: (1) financial literacy has a positive and significant effect on online lending practices, (2) financial behavior has a negative and insignificant effect on online lending practices, and (3) trust in online lending platforms has a positive but insignificant effect on online lending practices. The findings of this study provide practical implications for Generation Z, particularly women who are in the same age group as recent graduates or fresh graduates and are experiencing a transition toward independent financial management as private-sector employees, by encouraging more responsible use of online lending services through improved financial literacy. Furthermore, the results of this research can assist the government and regulators in formulating policies related to financial education and consumer protection in the digital lending sector, as well as serve as a reference for online lending platforms in developing more transparent and user-oriented services.